A case report of nasal lobular capillary hemangioma - Patel, Nikhilkumar D.; Mehta, Shivani M.; Trivedi, Dhruv A. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Nasal lobular capillary hemangiomas are rare and benign tumors of the paranasal sinuses. The aim is to study a case of nasal lobular capillary hemangioma. Here, a case of a 29-year-old male patient who presented to ear, nose and throat outpatient department (ENT OPD) with complaints of multiple episodes of epistaxis and left nasal obstruction for the past year. After proper radiological, cytological and hematological assessment, an excision biopsy from the mass of the left nasal cavity was performed which was suggestive of lobular capillary hemangioma. The patient has been operated on via lateral rhinotomy approach and nasal mass was found to be originated from the anterior ethmoidal artery, removed piecemeal and complete excision was done. Nasal lobular capillary hemangioma is quite a rare lesion of unknown etiology especially when it occurs in the nasal cavity. It should always be considered in the differential diagnosis of vascular lesions within the nasal cavity. Complete excision of the mass with a lateral rhinotomy approach gives an excellent outcome.